1999
DOI: 10.1590/s0036-46651999000600005
|View full text |Cite
|
Sign up to set email alerts
|

Jorge Lobo’s disease: experimental inoculation in Swiss mice

Abstract: SUMMARYSixty-four isogenic Swiss mice were intradermically inoculated in both hind foot pads. The inocula, consisting of fungal suspensions from biopsies obtained from Jorge Lobo's Disease patients, had the total number of fungi and the viability index determined using a Neubauer chamber and the fluorescein diacetate-ethidium bromide technique (FD-EB), respectively. The animals were sacrificed at times ranging from ten days to eighteen months after inoculation. The cellular infiltrate, mainly consisting of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Jorge Lobo's disease is a chronic deep mycosis whose prognosis in terms of survival is good, although treatment does not lead to complete cure of the infection [4,5]. Most patients present with long disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Jorge Lobo's disease is a chronic deep mycosis whose prognosis in terms of survival is good, although treatment does not lead to complete cure of the infection [4,5]. Most patients present with long disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Trauma and injuries or sites of insect bites facilitate penetration of the fungus. Lesion progression is slow, with new lesions arising contiguous to other lesions or through the lymphatic route [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, very little is understood about the conditions under which the pathogen grows and thrives, as well as its source and transmission route (Wiersema & Niemel 1965, Pang et al 2004, Lupi et al 2005, Paniz-Mondolfi et al 2007). Experimental inoculation attempts have been made using guinea pigs (Wiersema & Niemel 1965), hamsters (Wiersema & Niemel 1965, Opromolla & Noguiera 2000, tortoises (Geochelone denticulate, G. carbonaria and Kinosternon scorpioides; Sampaio et al 1971), monkeys (Macacca mulatta, M. nemestrina and M. fascicularis; Caldwell et al 1975), armadillos Euphractus sexcinctus (Sampaio & Braga-Dias 1977) and mice (Wiersema & Niemel 1965, Caldwell et al 1975, Opromolla et al 1999, Madeira et al 2000, 2003, Belone et al 2003, but many of those attempts yielded only short-term data on the development of the disease. Opromolla et al (1999) were able to successfully inoculate a Swiss strain of mice with lacaziosis and follow disease progression up to 18 mo post-inoculation; however, clinical presentation of the disease did not occur, and very few fungal cells were active by the end of the study.…”
mentioning
confidence: 99%
“…Experimental inoculation attempts have been made using guinea pigs (Wiersema & Niemel 1965), hamsters (Wiersema & Niemel 1965, Opromolla & Noguiera 2000, tortoises (Geochelone denticulate, G. carbonaria and Kinosternon scorpioides; Sampaio et al 1971), monkeys (Macacca mulatta, M. nemestrina and M. fascicularis; Caldwell et al 1975), armadillos Euphractus sexcinctus (Sampaio & Braga-Dias 1977) and mice (Wiersema & Niemel 1965, Caldwell et al 1975, Opromolla et al 1999, Madeira et al 2000, 2003, Belone et al 2003, but many of those attempts yielded only short-term data on the development of the disease. Opromolla et al (1999) were able to successfully inoculate a Swiss strain of mice with lacaziosis and follow disease progression up to 18 mo post-inoculation; however, clinical presentation of the disease did not occur, and very few fungal cells were active by the end of the study. Other studies have demonstrated that BALB/c mice may be a suitable animal model for studying the infectivity and aggression of the lacaziosis pathogen, as infection was sustained and lesions developed post-inoculation; however, all of the BALB/c inoculation studies maintained infection for a maximum of 18 mo before the animals were sacrificed, thereby supplying limited short-term data on the progression of lacaziosis (Madeira et al 2000, 2003, Belone et al 2003.…”
mentioning
confidence: 99%